Impact of the increase in the number of community pharmacists on their geographical distribution in Japan: a retrospective survey - Kazuhiro Iguchi; Midori Ueyama; Hiroto Nishio; Hirofumi Tamaki; Arihiro Osanai; Yoko Ino; Kazuya Nonomura; Megumi Horibe; Toshiyuki Matsunaga; Mitsuhiro Nakamura (Taylor & Francis Group, 2022)
Background Appropriate distribution of health care resources is required to adjust regional disparities in the quality of health care. Besides, the number of community pharmacists in Japan has increased recently, but the impact of this increase on the distribution of community pharmacists is unknown. Thus, we aimed at investigating the effect of the increase in the number of community pharmacists on the distribution per population and per area of inhabitable land. Methods Data from 2008 to 2018 were used. Equity among municipalities in the number of community pharmacists per population and per area of inhabitable land was assessed using the Gini coefficient. A mosaic plot was used to demonstrate the relationship between the population density and increase in the number of community pharmacists per municipality. Results The number of community pharmacists increased by approximately 1.3-fold from 2008 to 2018 in Japan. The Gini coefficient per population decreased gradually, whereas that per area increased slightly, with no change in distribution per area of inhabitable land. The number of community pharmacists per population increased regardless of the population density, but this increase per area was smaller for lower population density groups and larger for higher population density groups. Conclusion The increase in the number of community pharmacists has improved the distribution of community pharmacists per population, but not that per area of inhabitable land. The maldistribution of community pharmacists per area implies an imbalance in the distance between pharmacies and residents. Thus, there is need for measures to improve the distribution of community pharmacists.